Oxygen-generating electrode catalyst, anode electrode, and oxygen-generating device
A non-noble metal electrode catalyst, comprising silver and other elements, addresses the cost and resource constraints of noble metals by providing efficient and durable oxygen generation for green hydrogen production.
Patent Information
- Application Number
- JP2023108299
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-17
AI Technical Summary
Current electrode catalysts for oxygen generation in green hydrogen production rely on noble metals like platinum, ruthenium, and iridium, which are expensive and scarce, limiting the widespread adoption of green hydrogen as a clean energy source.
A non-noble metal electrode catalyst composed of a mixture of silver and two or more non-noble metal elements, such as manganese, iron, nickel, and zinc, with a cubic crystal system, oxygen vacancies, and multiple valence states, is developed, offering high oxygen generation efficiency and long life.
The catalyst achieves high oxygen generation efficiency, long life, and low cost, overcoming the resource and cost limitations of noble metals, with superior performance in slightly alkaline pH regions.
Smart Images

Figure 2025007109000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode catalyst for oxygen generation, an anode electrode, and an apparatus for generating oxygen. [Background technology]
[0002] In recent years, green hydrogen has been attracting attention as a clean energy source to replace fossil fuels in light of global environmental issues such as global warming. Green hydrogen is an environmentally friendly energy source that does not emit carbon dioxide during its production or use.
[0003] Since green hydrogen is produced by the electrolysis of water, an oxygen-evolving electrode catalyst is essential for producing green hydrogen. Currently, precious metals such as platinum group elements platinum (Pt), ruthenium (Ru) or iridium (Ir) are mainly used as electrode catalysts for oxygen generation, as disclosed, for example, in Patent Document 1. However, these precious metal elements are expensive and resources are limited, which is an obstacle to supplying a huge amount of green hydrogen. For this reason, there is a demand for a low-cost electrode catalyst for oxygen generation that is made of a non-noble metal, has high oxygen generation efficiency, and has a long life. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-37942 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a non-noble metal electrode catalyst which has high oxygen generation efficiency, a long life, and is also low in cost. [Means for solving the problem]
[0006] The configuration of the present invention for solving the problems is shown below.
[0007] (Configuration 1) An electrode catalyst for oxygen evolution comprising an oxide of a mixture containing silver and two or more non-precious metal elements, The silver is in the form of a cubic nanoparticle having a space group of Fm-3m; all of the non-noble metal elements have a plurality of valence states, including a species in the highest valence state that the non-noble metal elements can have; The electrode catalyst for oxygen evolution has oxygen vacancies. (Configuration 2) 2. The electrode catalyst for oxygen evolution according to claim 1, wherein the ratio of the oxygen vacancies is 40% or more and less than 100%. The ratio of oxygen vacancies was determined by measuring the O 1s spectrum of the oxygen evolution electrode catalyst by XPS, and dividing the O 1s spectrum by the lattice oxygen (O L ), and oxygen vacancy (O V ) and 533.7 eV surface adsorbed oxygen / interlayer water (O W ) and the lattice oxygen (O L ) is calculated by the area ratio. (Configuration 3) 3. The electrode catalyst for oxygen evolution according to claim 1 or 2, wherein the non-noble metal element is non-single crystal. (Configuration 4) The oxygen generating electrode catalyst according to any one of claims 1 to 3, wherein the oxide of the mixture further comprises a mixture of one or more selected from the group consisting of nitrides, sulfides, chlorides, and borides. (Configuration 5) 5. The oxygen evolution electrode catalyst according to any one of claims 1 to 4, wherein the nonmetallic metallic element is uniformly distributed. (Configuration 6) The oxygen evolution electrode catalyst according to any one of claims 1 to 5, wherein the silver is uniformly distributed. (Configuration 7) An anode electrode using the electrode catalyst for oxygen evolution according to any one of configurations 1 to 6. (Configuration 8) An oxygen generating device comprising the anode electrode according to configuration 7. Effect of the Invention
[0008] The present invention provides a non-precious metal electrocatalyst that has high oxygen generation efficiency, a long life, and is also low cost. [Brief description of the drawings]
[0009] [Figure 1] 1 is a SEM (Scanning Electron Microscope) photograph of a sample prepared in an example. [Diagram 2] 1 shows XRD (X-Ray Diffraction) data of samples prepared in the examples. [Diagram 3] These are the results of structural evaluation of the MnFeNiZn0.5AgOx sample prepared in the example. (a) is a low-magnification HR-TEM (High-Resolution Transmission Electron Microscope) image, (b) is a high-magnification HR-TEM image, (c) is an electron beam diffraction image of the area indicated by the circle, (d) is an ADF-STEM (Annular Dark-Field Scanning Transmission Electron Microscope) image, and (e) to (k) are observations of the spatial distribution of the component elements by EDS (Energy Dispersive Spectroscopy), where (e) is Mn, (f) is Fe, (g) is Ni, (h) is Zn, (i) is Ag, (j) is O, and (k) is Ti. [Figure 4] The results of XPS (X-ray photoelectron spectroscopy) measurements of the MnFeNiZn0.5AgOx sample prepared in the examples are shown here, along with the calculation results obtained by fitting the spectra corresponding to the actual measurements, (a) Mn 2p, (b) Fe 2p, (c) Ni 2p3 / 2, (d) Zn 2p3 / 2, (e) Ag 3d, and (f) O 1s. [Diagram 5]This is a characteristic diagram evaluating the oxygen evolution reaction of the MnFeNiZn0.5AgOx electrode catalyst in terms of the time dependence of potential, with pH as a parameter. [Figure 6] This is a characteristic diagram of the oxygen evolution reaction of the MnFeNiZn0.5AgOx electrode catalyst material evaluated by the potential-current characteristics (LSV curve) in an environment of 80°C using a 1M carbonate (Na-Ci) electrolyte. [Figure 7] This is a characteristic diagram comparing and evaluating the potential change over time (CP: Chronopotentiometry) of MnFeNiZn0.5AgOx and RuO2. [Figure 8] FIG. 2 is a configuration explanatory diagram illustrating the main configuration of the oxygen generating device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (Embodiment 1) In the first embodiment, the electrode catalyst of the present invention will be described.
[0011] The inventors conducted in-depth research into non-precious metal electrode catalysts for oxygen evolution and found that a material having the following characteristics has excellent properties as an oxygen evolution electrode catalyst (electrode catalyst), specifically, it has excellent overvoltage, durability, and large current characteristics in a weakly alkaline pH range.
[0012] (1) An oxide of silver (Ag) and a mixture containing two or more non-precious metal elements. (2) Silver is in the cubic crystal system of space group Fm-3m and in the form of nanoparticles. (3) all of the non-noble metal elements have multiple valence states, including a species in the highest valence state that the non-noble metal elements can have; (4) The electrode catalyst has oxygen vacancies. Here, a specific example of a material having the above characteristics (1) to (4) is an oxide mixture of manganese (Mn), iron (Fe), nickel (Ni), zinc (Zn), and silver (Ag), as shown in the examples described later.
[0013] When samples containing silver and those without silver were prepared and their properties were compared, it was found that the inclusion of silver significantly improved the electrochemical properties. For example, MnFeNiZn 0.5 O x and MnFeNiZn 0.5 AgO x After preparing the two materials and comparing their properties, 0.5 AgO x is highly active, and MnFeNiZn 0.5 O x The activity of the catalyst was higher than that of the catalyst itself.
[0014] Crystalline, nanoparticulate silver has high catalytic activity, and the nanoparticulate form also provides a large surface area relative to its volume, which is thought to have contributed to the high oxygen evolution reaction.
[0015] It is believed that the metal catalyst containing a plurality of non-precious metal elements produces a synergistic effect, resulting in the characteristic of high activity. There is no particular upper limit to the number of non-precious metal elements, but in consideration of ease of production and ease of quality control, the upper limit to the number of non-precious metal elements is 10, preferably 5.
[0016] It is believed that all non-precious metal elements, when having multiple valence states including the species with the highest valence state that the non-precious metal element can have, have the characteristic of having the effect of promoting the oxidation of the substrate to advance the oxygen evolution reaction.
[0017] The oxygen vacancy ratio is preferably 40% or more and less than 100%. It is believed that when the oxygen vacancy ratio is a high value of 40% or more, the number of active sites increases, resulting in the characteristic of high catalytic activity. The ratio of oxygen vacancies in the present invention is determined by measuring the O 1s spectrum of the oxygen evolution electrode catalyst by XPS, and dividing the O 1s spectrum by the lattice oxygen (O L ), and oxygen vacancy (O V ) and 533.7 eV surface adsorbed oxygen / interlayer water (O W) and the lattice oxygen (O L ) is defined as the area ratio of
[0018] By making the non-noble metal element amorphous or polycrystalline, i.e., non-single crystal, it becomes easier to manufacture the metal catalyst, and it becomes possible to reduce costs.
[0019] It is preferable that the nonmetallic metal elements and silver are uniformly distributed in terms of the stability over time of oxygen generation and the quality control of materials. If the distribution is uneven, the electrode is likely to deteriorate rapidly in some areas.
[0020] It is also preferred that the oxide of the mixture further contains a mixture of one or more selected from the group consisting of nitrides, sulfides, chlorides, and borides. The use of nitriding, sulfiding, chlorinating, and boriding solutions makes it possible to produce metal catalysts for oxygen generation at low cost. In addition, the presence of nitrides, sulfides, chlorides, and borides creates a synergistic effect, resulting in the characteristics of good activity, durability, and selectivity.
[0021] The electrode catalyst of the present invention can use metal elements that are abundant in resources and relatively low in cost, and does not contain rare and expensive precious metals such as platinum (Pt) and ruthenium (Ru), thereby reducing costs. Furthermore, by using the above-mentioned material configuration, a catalyst for oxygen generation electrodes is obtained that has excellent overvoltage, stability, durability, current density characteristics, specific charge, and large current characteristics in the weakly alkaline pH range, as shown in the examples.
[0022] The oxygen generating electrode catalyst (electrode catalyst) of the present invention can be obtained through a pyrolysis process in which a solution containing two or more non-precious metal elements and silver (Ag) is prepared and mixed, the mixture is applied to a conductive substrate such as titanium (Ti) by coating, and then the substrate is dried and fired. Here, as the solution containing two or more non-precious metal elements and silver (Ag), for example, a chloride solution or a nitrate solution can be used. In this case, the chlorine (Cl) used in the solution remains partially as an electrode catalyst, but it has been confirmed that it does not adversely affect the properties of the electrode catalyst, such as overvoltage and stability. By using a chloride solution, an oxygen generating electrode catalyst can be efficiently and easily produced. Regarding Ag, AgNO 3 can be used with preference. The sintering temperature is preferably 150° C. or higher and 400° C. or lower. Other methods for producing the electrode catalyst of the present invention include electrodeposition, chemical vapor deposition, hydrothermal synthesis, and solvothermal methods.
[0023] (Embodiment 2) In the second embodiment, an oxygen generating device 101 using the oxygen generating electrode catalyst explained in the first embodiment and an anode electrode (oxygen electrode) 12 used therein will be described with reference to FIG.
[0024] 8, the oxygen generating device 101 is equipped with an anode electrode (oxygen electrode) 12 and a cathode electrode (hydrogen electrode) 13, and its main components are an electrolytic cell 11 filled with water 14 containing an electrolyte, an oxygen gas separation tower 16, a dehumidifier 17, a water tank 18, a hydrogen gas separation tower 19, and a dehumidifier 20. A power source 15 is connected to the anode electrode 12 so that a positive voltage is applied to the cathode electrode 13, and a negative voltage is applied to the cathode electrode 13.
[0025] Water 14 is electrolyzed by applying a voltage to the anode electrode 12 and the cathode electrode 13 , and oxygen gas and hydrogen gas are generated within the electrolytic cell 11 . The generated oxygen gas is transported together with water vapor to the oxygen gas separation tower 16, where the moisture and oxygen gas are separated. The separated water is poured into a water tank 18, and the oxygen gas is dehumidified by a dehumidifier 17 to remove oxygen (O 2 ) is recovered. Here, the separation of oxygen gas or oxygen gas from water can be performed using a density difference separation method that separates water, which is a high-density liquid, from gas, which is low-density, by the action of gravity or collision force, and / or a gas-liquid separation method that utilizes the surface tension of the liquid.
[0026] The generated hydrogen gas is transported together with water vapor to the hydrogen gas separation tower 19, where the moisture and hydrogen gas are separated. The separated water is poured into the water tank 18, and the hydrogen gas is dehumidified by the dehumidifier 20 to obtain hydrogen (H 2 The water supplied via the pipe 21 and the water poured from the oxygen gas separation tower 16 and the hydrogen gas separation tower 19 are returned to the electrolytic cell via the water tank 18.
[0027] Here, the anode electrode 12 is an electrode that uses an electrode catalyst having the characteristics described in embodiment 1. That is, as the anode electrode 12, an electrode in which the material described in embodiment 1 is deposited on a collector electrode substrate such as titanium, or an electrode made of the material described in embodiment 1 is used.
[0028] The oxygen generating device 101 equipped with the anode electrode 12 using the oxygen generating electrode catalyst described in embodiment 1 is an oxygen generating device 101 that has excellent characteristics such as overvoltage, stability, durability, current density characteristics, specific charge, and large current characteristics in the weakly alkaline pH range, has high oxygen generating efficiency, a long life, and is also low in cost. EXAMPLES
[0029] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0030] 1. Electrocatalyst Preparation The oxide of a mixture of manganese (Mn), iron (Fe), nickel (Ni), zinc (Zn), and silver (Ag) (hereinafter referred to as MnFeNiZnAgO xAn electrode catalyst made of a ZnO-based material was prepared by the following process. As will be described later, this material has the following characteristics as an electrode catalyst material defined in the first embodiment. (1) An oxide of silver and a mixture containing two or more non-precious metal elements. (2) Silver is in the cubic crystal system of space group Fm-3m and in the form of nanoparticles. (3) all non-precious metal elements have multiple valence states, including a species in the highest valence state that the non-precious metal elements can have; (4) The electrode catalyst has oxygen vacancies.
[0031] Specifically, MnFeNiZnAgO is produced by the following process. x A sample was prepared using the above-mentioned material as an electrode catalyst. First, 0.05M MnCl 2 , FeCl 2 , NiCl 2 , ZnCl 2 and AgNO 3 Each solution was prepared. Next, the solutions were mixed according to the ratio. 0.5 AgO x The preparation of MnCl 2 :FeCl 2 :NiCl 2 :ZnCl 2 :AgNO 3 Mixed in a ratio of 1:1:1:0.5:1. The mixture was then drop-cast onto a Ti substrate measuring approximately 0.5cm x 2.0cm x 0.01cm, dried at room temperature (approximately 25°C), and pre-sintered in an oven at 350°C for 10 minutes. This step of drop-casting the mixture and pre-sintering was repeated nine times, and then sintered at 450°C for one hour to produce an electrode coated with an electrode catalyst containing five types of metals on a Ti substrate. Here, the pre-sintering and sintering were performed in air. Thus, oxidation was achieved by natural oxidation, pre-sintering, and sintering.
[0032] For comparison, RuO 2A metal oxide catalyst was prepared. RuO 2 Metal oxide catalysts were prepared by mixing the above five metal solutions in a 0.05M solution of RuCl 3 Replace with RuO and follow the above procedure for the rest. 2 A catalyst coated electrode was prepared. The mass loading of the electrode coated with the electrocatalyst on the Ti substrate was approximately 0.13 mg for all samples.
[0033] 2. Characterization 2.1 Material characterization The SEM (Scanning Electron Microscope) photographs of the prepared electrode samples are shown below. 0.5 AgO x An example is shown in Figure 1. Nanoparticles can be seen, and the surface has irregularities. Here, an SU8000 (manufactured by Hitachi) was used as the SEM. As a result of measuring each sample by XRD (X-ray Diffraction), it was found that the crystal structure of the prepared sample was composed of cubic silver chloride with space group Fm-3m and hexagonal nickel oxide with space group R-3m, as shown in Figure 2. Here, a MiniFlex X-ray diffractometer (manufactured by Rigaku) was used for this measurement. For reference, Figure 2 shows the crystal structure of Sc 0.5 MnFeNiAgO x and Ti 0.5 MnFeNiAgO x The XRD measurement results are also shown. The results of observing the sample using a cross-sectional high-resolution transmission electron microscope (HR-TEM) are shown in Fig. 3(a). 0.5 AgO x The average thickness of the nanoparticles was 978.0±139.8 nm. As the black spots were observed, it was found that the nanoparticles were composed of nanoparticles. The HR-TEM used was JEM-2100F1 (manufactured by JEOL).
[0034] The results of detailed observation by Selected Area Electron Diffraction (SAED) are shown in Figures 3(b) and (c), which indicate that the materials other than the AgCl crystals are mainly amorphous or low-crystalline materials. The main SAED pattern, as shown in Figure 3(c), corresponds to the three-dimensional structure of AgCl, and this result is in good agreement with the XRD measurement result shown in Figure 2. MnFeNiZn 0.5 AgO x The results of observation with an annular dark field-scanning transmission electron microscope (ADF-STEM) are shown in Figure 3(d), and the results of element mapping using energy dispersive spectroscopy (EDS) are shown in Figures 3(e)-(k). Here, Figures 3(e), (f), (g), (h), (i), (j), and (k) show the distribution of Mn, Fe, Ni, Zn, Ag, O, and Ti elements, respectively. These results indicate that the elements Mn, Fe, Ni, Zn and O are uniformly distributed throughout the electrocatalyst. On the other hand, most of the Ag element is in the form of nanoparticles, with only a small amount forming metal oxides with other metal species and dispersed therein. The ADF-STEM used was JEM-ARM200F-B (manufactured by JEOL).
[0035] Next, high-resolution X-ray photoelectron spectroscopy (XPS) was used to characterize the MnFeNiZn 0.5 AgO x The chemical composition and oxidation state of each element were investigated. The results are shown in Figure 4. Here, a Quantera SXM (Ulvac-PHI) was used for XPS. As a result, MnFeNiZn 0.5 AgO xThe XPS measurement results confirmed that the sample contains seven elements: Mn, Fe, Ni, Zn, Ag, Cl, and O. Figure 4 shows the spectra of the six elements: Mn, Fe, Ni, Zn, Ag, and O. As shown in FIG. 4(a), Mn 3+ 641.9 eV (Mn 2p 3 / 2 ) and 653.6 eV (Mn 2p 1 / 2 ), and Mn 4+ 646.7 eV (Mn 2p 3 / 2 ) and 658.4 eV (Mn 2p 1 / 2 ) and Fe has two oxidation states, Fe 2 , as shown in Fig. 4(b). 2+ 711.0 eV (Fe 2p 3 / 2 ) and 724.1 eV (Fe 2p 1 / 2 ), and Fe 3+ 713.0 eV (Fe 2p 3 / 2 ) and 726.1 eV (Fe 2p 1 / 2 ) It consists of two oxidation states. Ni 2p 3 / 2 As shown in Fig. 4(c), 2+ 856.2 eV and Ni 3+ It consists of two states at 858.9 eV, Zn 2p 3 / 2 As shown in Fig. 4(d), Zn 2+ 1022.0 eV and Zn 0 It consists of two states at 1023.6 eV. As shown in Figure 4(e), Ag 2+ 367.3 eV (Ag 3d 5 / 2 ) and 373.3 eV (Ag 3d 3 / 2 ), and Ag + 368.1 eV (Ag 3d 5 / 2 ) and 374.1 eV (Ag 3d 3 / 2 ) It consists of two oxidation states.
[0036] From the above results, MnFeNiZn 0.5 AgO x The sample contains five metal elements, Mn, Fe, Ni, Zn, and Ag, each of which has multiple valence states.4+ Or Ag 2+ It was shown that they are distributed mainly with species in the highest valence state, such as
[0037] In addition, as shown in Fig. 4(f), the O 1s spectrum was calculated by subtracting the lattice oxygen (O L ), and oxygen vacancy (O V ) and 533.7 eV surface adsorbed oxygen / interlayer water (O W ) and deconvolution analysis is performed, 0.5 AgO x The oxygen (O) in the sample is oxygen vacancy (O V ) was as high as 48 atomic %, indicating that this sample had a large number of oxygen vacancies.
[0038] From the above evaluation, MnFeNiZn 0.5 AgO x The sample is (1) An oxide of silver (Ag) and a mixture containing two or more non-precious metallic elements (Mn, Fe, Ni, Zn), (2) Silver is in the cubic crystal system of space group Fm-3m and in the form of nanoparticles. (3) all non-precious metal elements have multiple valence states, including a species in the highest valence state that the non-precious metal elements can have; (4) It is understood that the material has oxygen vacancies and has the characteristics defined in the first embodiment.
[0039] 2.2 Electrochemical characterization MnFeNiZnAgO x , MnFeNiZn 0.5 AgO x and MnFeNiZnAg 0.5 O x MnFeNiZnAgO x For the system material, its 10mA / cm 2The overpotential at 1000 kV was evaluated. The measurement was carried out using a three-electrode beaker cell consisting of a working electrode with the above-mentioned material placed thereon, a reference electrode, and a counter electrode, and 0.1 M KOH as the electrolyte. The reference electrode was a silver-silver chloride electrode, and the counter electrode was platinum. As a result, MnFeNiZnAgO x , MnFeNiZn 0.5 AgO x , MnFeNiZnAg 0.5 O x The overvoltages of MnFeNiZnAgO are 0.45 V, 0.42 V and 0.44 V, respectively. x The material had excellent overvoltage properties.
[0040] Next, MnFeNiZn 0.5 AgO x The electrochemical stability of the samples was evaluated by chronopotentiometry. 2 The time dependence of the voltage E at which the hydrogen peroxide is obtained was evaluated by controlling the pH of the electrolyte with a buffer solution. Here, the voltage E is the voltage applied to a reversible hydrogen electrode (RHE). As is clear from the results shown in Figure 5, in an electrolyte environment controlled at pH ≦ 8 with phosphate buffer, the voltage E increased rapidly within 1 hour. 0.5 AgO x It has been confirmed that the electrode made of the sample deteriorates rapidly during the oxygen evolution reaction, causing Mn, Fe and Ni to dissolve and flow into the electrolyte. On the other hand, in an electrolyte environment controlled to an alkaline pH of 9.2 or higher using carbonate or KOH buffers, the current is 50 mA / cm 2 The high durability and stability of the sample have been ensured, allowing it to maintain this temperature for more than three hours. It has been confirmed that the distribution and composition of all the elements in this sample remain almost unchanged before and after the experiment.
[0041] The electrochemical stability can be significantly enhanced by controlling the electrolyte environment at 80° C. and pH 9.2 with 1.0 M Na-Ci buffer. Figure 6 shows the MnFeNiZn 0.5 AgO x The results of LSV (Linear Sweep Voltammetry) measurements performed on the sample under these conditions are shown below. The voltage E was 2.6 V relative to RHE, and the current was 1000 mA / cm. 2 was obtained.
[0042] Figure 7 shows the results of the MnFeNiZn 0.5 AgO x The sample was evaluated by chronopotentiometry, where the current was 400 mA / cm 2 The temperature was set to 0°C, and the electrolyte was added at the timing indicated by the arrow. 2 The results of are also shown as comparative examples. As is clear from FIG. 0.5 AgO x The sample was 400mA / cm 2 The voltage E was stable for more than 600 hours at 1000 V. On the other hand, the voltage E of RuO 2 In the sample, the voltage E changed rapidly after 7 hours, and the MnFeNiZn 0.5 AgO x The superiority of the sample was confirmed.
[0043] MnFeNiZn 0.5 AgO x The specific charge of the sample was measured by electrochemical measurement and found to be 1×10 8 C / g~1×10 9 C / g, RuO 2 1×10 7 C / g~5×10 8 C / g, and from the standpoint of specific charge, MnFeNiZn 0.5 AgO x The sample was excellent as an electrocatalyst for acid generation.
[0044] From the above, it is possible to obtain a MnFeNiZnAgO having the structure defined in the first embodiment. x It was confirmed that the material based on this system has excellent properties as an electrode catalyst for oxygen evolution. [Industrial Applicability]
[0045] Metal catalysts for oxygen generation are used in equipment that produces green hydrogen, which is seen as the next-generation energy source, and are also applied to fuel cells, FCVs, etc. The present invention provides a metal catalyst with high oxygen generation efficiency without using platinum group precious metal elements, which are rare, expensive, and limited in resource. It is expected that this will support next-generation industry and society, regardless of whether it is for consumer or industrial use, and greatly contribute to their development. [Explanation of symbols]
[0046] 11: Electric field cell 12: Anode electrode (oxygen electrode) 13: Cathode electrode (hydrogen electrode, RHE) 14: Water (H 2 O) 15: Power supply 16: Oxygen gas separation tower 17:Dehumidifier 18: Water tank 19: Hydrogen gas separation tower 20:Dehumidifier 21: Piping
Claims
1. An electrode catalyst for oxygen evolution comprising an oxide of a mixture containing silver and two or more non-precious metal elements, The silver has a cubic crystal system of space group Fm-3m and is in the form of nanoparticles; all of the non-noble metal elements have a plurality of valence states, including a species in the highest valence state that the non-noble metal elements can have; The electrode catalyst for oxygen evolution has oxygen vacancies.
2. 2. The oxygen evolution electrode catalyst according to claim 1, wherein the ratio of the oxygen vacancies is 40% or more and less than 100%. The ratio of oxygen vacancies was determined by subjecting the oxygen evolution electrode catalyst to an XPS measurement to obtain an O 1s spectrum, which was then converted into the lattice oxygen (O L ), 531.8 eV oxygen vacancy (O V ) and 533.7 eV surface adsorbed oxygen / interlayer water (O W ) and the lattice oxygen (O L ) is calculated by the area ratio.
3. 3. The electrode catalyst for oxygen evolution according to claim 1, wherein the non-noble metal element is non-single crystalline.
4. 4. The electrode catalyst for oxygen generation according to claim 1, wherein the oxide of the mixture further comprises a mixture of one or more selected from the group consisting of nitrides, sulfides, chlorides and borides.
5. The oxygen evolution electrode catalyst according to claim 1 , wherein the non-metallic metallic element is uniformly distributed.
6. The oxygen evolution electrode catalyst according to claim 1 , wherein the silver is uniformly distributed.
7. An anode electrode using the electrode catalyst for oxygen evolution according to any one of claims 1 to 6.
8. An oxygen generating device comprising the anode electrode according to claim 7.
Citation Information
Patent Citations
Method for producing fuel cell electrode catalyst, fuel cell electrode catalyst and use of the same
JP2013037942A